1999
DOI: 10.1007/s005950050370
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Positive Peritoneal Lavage Cytology Findings in the Stage Grouping of Gastric Cancer

Abstract: Although peritoneal lavage cytology is widely performed during surgery for gastric cancer and the results have been reported to be one of the accurate prognostic factors, the cancer stage is determined independent of the results of lavage cytology according to the First English Edition of Japanese Classification of Gastric Carcinoma. In this study we demonstrated the validity of lavage cytology for accurately staging gastric cancer. Between 1988 and 1996, peritoneal lavage cytology was performed in 347 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 0 publications
0
9
1
7
Order By: Relevance
“…22 In a large series of 347 patients, the rate of positive peritoneal lavage cytology was only 8.4%, but there was a clear correlation with poorer survival rates. 23 In the present study, the incidence of patients with tumor cells in the peritoneum was higher than this, but we could not confirm the finding of a lower survival rate. Peritoneal lavage fluid was collected from fewer patients than bone marrow aspirate, and these numbers were probably insufficient to evaluate significant survival differences in the subset of patients with T1 or T2 tumors.…”
Section: Discussioncontrasting
confidence: 82%
“…22 In a large series of 347 patients, the rate of positive peritoneal lavage cytology was only 8.4%, but there was a clear correlation with poorer survival rates. 23 In the present study, the incidence of patients with tumor cells in the peritoneum was higher than this, but we could not confirm the finding of a lower survival rate. Peritoneal lavage fluid was collected from fewer patients than bone marrow aspirate, and these numbers were probably insufficient to evaluate significant survival differences in the subset of patients with T1 or T2 tumors.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous reports have stated that the prognosis in surgically treated patients with gastric carcinoma is significantly affected by the presence of IFCCs at the time of gastrectomy. 6,[8][9][10][12][13][14][15]18,19 The survival rate also appears to be related to the number and the arrangement of IFCCs, that is, clustered, isolated, or clustered-plus-isolated type. 10 None of our patients who had IFCCs survived longer than 17 months after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…According to the current AJCC staging classification of both gastric and esophageal cancer, peritoneal cytology is not considered in the TNM classification; however, in multiple studies positive cytology portends a worse prognosis [1,6,16], and the Japanese Classification of Gastric Cancer now includes cytology as an indicator of stage IV disease [8]. Furthermore, the presence of positive cytology has been offered as an indication for a more thorough lymph node dissection or selection for adjuvant treatment involving intraperitoneal instillation of chemotherapeutics [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant cells are present in 7.5-41% of peritoneal lavage specimens in patients with gastric cancer, and studies have shown that the presence of malignant cells may be the only positive finding in 6-29% of patients undergoing staging laparoscopy [2,13]. According to the current American Joint Commission on Cancer (AJCC) staging classification of both gastric and esophageal cancer, peritoneal cytology is not considered in the TNM classification; however, in multiple studies positive cytology portends a worse prognosis [1,6,16], and the Japanese. Classification of Gastric Cancer now includes cytology as indicator of stage IV disease [8].…”
mentioning
confidence: 99%